Building professional learning communities of foreign language teachers in higher education - Wen, Qiufang; Zhang, Hong (Círculo de Lingüística Aplicada a la Comunicación, 2020)
In recent decades there has been increasing interest in identifying the critical features of effective professional learning communities (PLCs). This identification is useful for evaluating the quality of a PLC, but not for building one. This study aims at describing a conceptual model for developing a new PLC, illustrating its application with an example. The model is explained in terms of four constitutive elements (PARTICIPANTS, OBJECTIVES, MEDIATORS, and MECHANISM), and their interactive relations. The development of a PLC of foreign language teachers (PLC-FLTs) at Beijing Foreign Studies University is used to illustrate how the model can function successfully. The illustration is coupled with a discussion of the PLC’s decades of experience in collective leadership, management of the four elements, and tips for tackling various challenges in keeping the PLC going.